Illegal drug use is associated with poorer life satisfaction and self-rated health (SRH) in young people - Kang, Weixi (Frontiers in Psychiatry, 2023)
Illegal drugs can bring negative health and psychological health consequences to people who use them. However, much less is known about illegal drug use and its association with life satisfaction and self-rated health (SRH) in young people in the context of the United Kingdom, which is important because SRH and life satisfaction are associated with important outcomes including morbidity and mortality. By analyzing data from a nationally representative sample with 2173 people who do not use drugs and 506 people who use illegal drugs aged between 16 to 22 (mean=18.73±1.61) years old from Understanding Society: the UK Household Longitudinal Study (UKHLS) using a train-and-test approach and one-sample t-tests, the current study found that illegal drug use is negatively associated with life satisfaction (t(505)=-5.95, p<0.001, 95% C.I. [-0.58, -0.21], Cohen’s d=-0.26) but not with SRH. Intervention programs and campaigns should be developed to prevent people from using illegal drugs, which may then avoid the negative consequence of poor life satisfaction associated with illegal drug use.